PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN BANK PERKREDITAN RAKYAT DI INDONESIA - Bobby G. H. Kangmartono; Meina Wulansari Yusniar; Sufi Jikrillah (Universitas Lambung Mangkurat, 2018)
This research is aimed to analyze the influence of Corporate Governance (CG) mechanism consisting of Capital Adequacy Ratio (X1), Number of Board of Commissioner (X2), Number of Board of Directors (X3) as independent variables toward financial performance of Rural Bank (Y) as dependent variable in Indonesia either simultaneously or partially during 2015 to 2016. The population in this study are all Rural Banks (BPR) operating in Indonesia according to Statistics of National Banking 2016. The sample was selected using purposive sampling obtained 50 BPRs with the largest total assets nationally. This study uses secondary data which is the BPR's financial report 2015-2016 published in Bank Indonesia Directory and Otoritas Jasa Keuangan websites. Hypothesis testing in this study using classical assumption test, multiple linear regression with α 0,05, which determine, fit test model (F test), and t test with SPSS Program. The results of this study indicate that partially, Capital Adequacy Ratio and the number of Board of Commissioners have significant positive effects to BPR financial performance, while the number of Board of Directors has a significant negative effect on the financial performance of BPR.